Pendidikan Islam dan Era Society 5.0 ; Peluang dan Tantangan Bagi Mahasiswa PAI Menjadi Guru Berkarakter - Idris, Muhammad (Belajea: Jurnal Pendidikan Islam, 2022)
This article describes Islamic education and the era of Society 5.0 as well as opportunities and challenges for PAI students in achieving qualified teachers.Â This study uses library research methods using content analysis techniques and using a hermeneutic approach. This article produces several findings including: If the era of society tries to eliminate the gaps in social problems faced by humans as a result of technological advances, then Islamic education always carries the vision of rahmatan lil ’alamin. Then, the era of society 5.0 is not something that is feared by PAI students, because there are several opportunities to create teachers with character, including: Facilitating access to self-potential development and competence, Opening new jobs, Accelerating the development of Islamic educational institutions, The need for spiritual dimensions humans, the tendency to be more open and rational. Besides that, there are also several challenges, including: High potential for individuality, Speed competition, Expertise in IT, Ability to overcome various challenges faced and the emergence of multiple understandings. PAI teachers who have the character that students aspire to, of course, are not limited to educational institutions but are more oriented to the vision and mission of Islamic Education itself, namely rahmatan lil ’alamiin and carry the mission of happiness in the world and the hereafter.